PENINGKATAN KEMAMPUAN MENULIS TEKS EKSPOSISI MELALUI MODEL PROBLEM BASED LEARNING PADA SISWA SD - Khaera Umma; Muhammad Akhir; Amal Akbar (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study aims to improve the exposition text writing skills of fifth-grade students at UPT SPF SDN Minasa Upa through the implementation of the Problem Based Learning (PBL) model. The low ability of students to write exposition texts served as the background for conducting this research. The PBL model is expected to help students more easily understand the material and become proficient in writing exposition texts. The type of research used is Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of four stages: planning, action implementation, observation and evaluation, and reflection. The research subjects consisted of 29 fifth-grade students. Data collection techniques were carried out through observation, writing tests, and documentation. Data were analyzed descriptively using quantitative and qualitative methods. The research results showed a significant improvement in students' exposition text writing skills. In cycle I, learning completeness only reached 27.5% (8 students), while 72.4% (21 students) had not yet achieved mastery. After improving the learning process in cycle II, completeness increased to 86.2% (25 students) with only 13.7% (4 students) not yet achieving mastery. The improvement was also evident in students' active participation, ability to identify problems, and motivation to write. Thus, the implementation of the Problem Based Learning (PBL) model proved effective in improving the exposition text writing skills of fifth-grade students at UPT SPF SDN Minasa Upa.